Consumer Protection In Power Purchase Agreement In Standard Agreement Perspective - Muljono, Bambang Eko; Sastradinata, Dhevi Nayasari; Winarno, Jatmiko; Rupawanti, Nadia (Universitas Islam Lamongan, 2024)
Solar energy provides consumers with the ability to generate their own electricity, Indonesia has 0.31 GW of solar power capacity, just shy of 0.03 percent of its total solar potential. Looking forward, the country plans to add up to 4.5 GW of solar capacity by 2030 in the PLN's Electricity Business Plan (RUPTL) 2021-2030, In the power purchase agreement, the above is not clearly stated in the clauses of the agreement, so it can cause multiple interpretations. The balance of the position of the parties in the standard power purchase contract between PT. PLN (PERSERO) with customers has not yet been fully realized. This is indicated that there are still articles in the power purchase agreement between PT. PLN (PERSERO) with customers, which are articles that only prioritize the interests of PT. PLN (PERSERO), which in this case is the party making the standard agreement. The Consumer Protection Law does not regulate Standard Agreements but regulates the contents of standard agreements called Standard Clauses.